2020
DOI: 10.1038/s41525-020-0125-4
|View full text |Cite
|
Sign up to set email alerts
|

19p loss is significantly enriched in older age neuroblastoma patients and correlates with poor prognosis

Abstract: Genomic aberrations of neuroblastoma occurring in late childhood and adolescence are still understudied. Publicly available DNA copy number profiles of 556 tumors (discovery set) and of 208 tumors obtained by array-CGH assay (validation set) were used to test if 19p loss is significantly over-represented in children and adolescents with neuroblastoma. The 19p loss occurrence was separately tested within different age groups in the discovery and validation set and the resulting P values were combined by metaana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…Genetic risk factors previously identified in primary NB include larger chromosomal aberrations, such as amplification of the MYCN oncogene, 11q-deletion, 1p-deletion, and 17q-gain 3 , as well as activating mutations in ALK encoding anaplastic lymphoma kinase 4 8 . Additional genomic alteration that recently have been associated to inferior outcome are distal 6q-deletion 9 , 10 , 19p-deletion and 1q-gain 11 , 12 and aberrations connected to ATRX , TERT , TP53 or RAS 13 . Analysis of primary NB tumors indicates a relative paucity of recurrent somatic alterations, with mutations in ALK being most frequent 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic risk factors previously identified in primary NB include larger chromosomal aberrations, such as amplification of the MYCN oncogene, 11q-deletion, 1p-deletion, and 17q-gain 3 , as well as activating mutations in ALK encoding anaplastic lymphoma kinase 4 8 . Additional genomic alteration that recently have been associated to inferior outcome are distal 6q-deletion 9 , 10 , 19p-deletion and 1q-gain 11 , 12 and aberrations connected to ATRX , TERT , TP53 or RAS 13 . Analysis of primary NB tumors indicates a relative paucity of recurrent somatic alterations, with mutations in ALK being most frequent 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…These observations showed that phenotypic NUC inhibition in ADRN-type NB could generate disparate transcriptomic alterations. In DCX -KD cells, the down-regulated genes showed positional enrichment for NB-relevant regions of loss of heterozygosity ( Mora et al, 2001 ; White et al, 2001 ; Lasorsa et al, 2020 ), including 19p13, 19q13, and 1p36 (Table S1). We checked the literature on NB for similar observations and found that a link between MYCN down-regulation and oxphos inhibition was identified previously in MNA NB cells ( Dzieran et al, 2018 ; Oliynyk et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Better outcomes were observed among patients aged less than 2 years compared with older patients even though there was no statistically significant in our study due to the limited number of patients. We believe that this finding may be attributed to older patients commonly having molecular markers of poor prognosis, such as deletion of chromosome 19p [ 14 ]. Younger neuroblastoma patients may be good candidates for ASCT in countries with limited resources.…”
Section: Discussionmentioning
confidence: 99%